Modeling The Determinants Of Man-Made Attraction Selection And Revisit Intention In Alfonso Lista, Ifugao: An Exploratory, Confirmatory And Causal Analysis - Mark John D. Calica; Jhun Lemuel B. Gordolan; Reymark R. Miguel; David Gerome N. Pauig; Joshua C. Tubiera; Client William M. Malinao (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Tourism remains a key driver of local economic development and cultural vitality, yet the sustainability of man-made destinations depends on understanding what attracts visitors. Thus, this study examined the factors influencing tourists’ selection and revisit intentions to man-made attractions in Alfonso Lista, Ifugao, Philippines, specifically the 1K Step and Magat Wetland Ecotourism Parks. The objectives were to (1) identify attraction factors, (2) determine visitor challenges, (3) assess the average number of visits, and (4) identify predictors of visitation frequency. Using a descriptive and causal research design, data were gathered from 299 actual tourists through a patterned structured questionnaire. Data were analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), descriptive statistics, and Multiple Linear Regression (MLR). EFA revealed five key constructs, accounting for 72.7% of the total variance (KMO = 0.874, p < .001). While CFA validated the model with an excellent fit (CFI = 0.95, RMSEA = 0.052). Tourists strongly agreed on the importance of safety, beauty, and accessibility. Although the potentials were not realized, challenges were noted, including limited accommodation, poor transportation services, and weak infrastructure. Regression results indicated that Environmental and Aesthetic Appeal (β = 0.42, p = .001) and Accessibility and Infrastructure (β = 0.35, p = .003) significantly predicted the average number of visits (R² = 0.48). The study confirms that aesthetics and accessibility are powerful drivers to attract visitors to selected attraction sites in Alfonso Lista, Ifugao, Philippines. Results advocate for infrastructure enhancement, digital visibility, and sustainable tourism design to elevate Alfonso Lista’s competitiveness in the Cagayan Valley tourism circuit.